Analisis Fungsi Produksi Ces (Constant Elasticity OfSubstitution) Industri Kerajinan Genteng Di DesaKaranggeneng Kabupaten Boyolali - Rosdiana, Ita, Dr. Agung Riyardi, M.Si (2017)
This study aimed to analyze the influence of the male labor force and total employment of women to the amount produced, and analyze how the elasticity of the tile production in the handicraft industry in the village Karanggeneng Boyolali. The data used in this research is primary data and secondary data. The primary data obtained directly through interviews and secondary data obtained from the district office and BPS Boyolali. The analytical method used is multiple regression analysis using a model of the production function CES (Constant Elasticityof Substitution). Regression analysis showed that the labor of men and women workers jointly affect the amount of production can be seen from the significant F value of 0.0000. There is a positive and significant effect on male labor to total tile production produced. There is a negative and significant impact on women's employment to total tile production in the village Karanggeneng. Subtitusinya elasticity value of 0.188 <1 (inelastic), meaning that employers tile craft is difficult to do because the workforce reduction will affect the amount of the resulting tile production.